Facile Preparation of Varisized ZIF‐8 and ZIF‐8/Polypyrrole Composites for Flexible Solid‐State Supercapacitor. Issue 25 (1st September 2017) - Li, Haowen; Fu, Dongying; Zhang, Xian‐Ming; Han, Gaoyi; Zhang, Fengwei
Abstract: We have successfully synthesized zeolitic imidazolate framework‐8 (ZIF‐8) with controlled sizes and morphology by a facile method in methanol solution. Then the varisized ZIF‐8 coated on the carbon nanotube film (CNTF) and further electrochemically deposited polypyrrole (PPy) to give flexible porous electrodes (noted as PPy/XZIF‐8‐CNTF). Electrochemical dates show that the PPy/lZIF‐8‐CNTF electrode prepared by large size ZIF‐8 exhibits an exceptional areal capacitance (264.8 mF cm −2 ) at the current density of 1.0 mA cm −2 . We also assembled and tested a PPy/lZIF‐8‐CNTF symmetric solid‐state supercapacitor, which shows excellent areal capacitance (143.3 mF cm −2 ) at the current density of 0.4 mA cm −2 . The device also exhibits good cycle stability and flexibility. Abstract : PPy/ZIF‐8 is synthesized and used as electrode materials.The PPy and ZIF‐8 exists synergistic effect in the PPy/ZIF‐8‐CNTF composites.PPy/lZIF‐8‐CNTF has excellent properties for flexible supercapacitors.